Handbook on prisons - Jewkes, Yvonne; Crewe, Ben; Bennett, Jamie (Routledge, 2016)
pt. 1. Prisons in context -- pt. 2. Prison controversies -- pt. 3. International perspectives on imprisonment -- pt. 4. The penal spectrum.